Nano Coating of Aloe-Gel Incorporation Additives to Maintain the Quality of Freshly Cut Fruits - Suriati, Luh (Frontiers in Sustainable Food Systems, 2022)
Edible coating is an environmentally friendly technology that is applied to fresh-cut fruit products. One of the natural ingredients that has the potential as an edible coating is Aloe-gel because it contains several functional components. The main advantage of using edible coating of Aloe-gel (Aloe-coating) is that additives can be incorporated into the polymer matrix to enhance its properties. Additives can improve the safety, nutritional, and sensory attributes of fresh fruits. However, in some cases, Aloe-coating does not work. Particle size determines the effectiveness of the coating process on fresh-cut fruits. Nano-coating Aloe-gel can be used to overcome the difficulty of adhesion of coating materials on the surface of fresh-cut fruits. Quality criteria for fresh-cut fruit coated with nano-coating of Aloe-gel must be strictly defined and quality parameters must be monitored during storage. Discoloration, loss of firmness, spoilage ratio, and weight loss of coated fruit were monitored. This review discusses the use nano-coating of Aloe-gel which is incorporated with additional ingredients to maintain the quality of fresh-cut fruits. It also includes recent advances in preparation, extraction, stabilization, and application methods of Aloe-gel nanocoating